Bugs, tariffs and colonies: The political economy of wine trade 1860 - 1970 - Giulia Meloni; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2016)
The 1860 - 1970 period is a particularly interesting period to study wine trade because of dramatic changes in the wine markets and trade over the course of a century. The dramatic changes in trade flows were caused by both "nature" and "men". Mediterranean wine trade represented around 90% of global wine trade and France was the world's leading exporter. The arrival of Phylloxera devastated French vineyards and stimulated Spanish and Italian wine exports. When French wine production recovered, French winegrowers pressured their government to intervene, resulting in high tariffs on Spanish and Italian wines and Greek raisins. The protectionist trade regime contributed to the bankruptcy of Greece and to the substitution of wine trade from Spain and Italy to France's North African colonies. When Algeria, Morocco and Tunisia became independent, France imposed high wine tariffs, effectively killing their wine exports. The decline of the wine industry in North Africa coincided with the trade and policy integration of the South European wine exporters in the EEC - the predecessor of the EU.
Keywords: 330; Weinhandel; Weinbau; Schädling; Zollpolitik; Protektionismus; Mittelmeerraum